Research on Coupling Degree Model of Safety Risk System for Tunnel Construction in Subway Shield Zone. (18th December 2019) - Pan, Haize; Gou, Jing; Wan, Zihong; Ren, Chuxuan; Chen, Mengjie; Gou, Tangqiao; Luo, Zhenhua
Abstract : Due to the complexity of construction technology and the seriousness of the safety situation in subway tunnels, it is urgent to find a risk-control method to monitor and evaluate the construction safety risk system of the subway shield tunnel and to avoid the occurrence of safety risk accidents. Based on the fuzzy entropy theory, this paper establishes a comprehensive index system for the construction safety risk system of shield tunnels. Also, in order to quantitatively analyze the coupling degree among various factors in the safety risk system, the calculation model of coupling degree is established based on the theory of coupling degree in physics. Taking Tianjin subway project as an example, the coupling degree of its safety risk system is calculated. The result shows that the coupling degree of the safety risk system is 0.6997, which indicates that the whole safety risk system is in high-risk coupling level. Due to the system in an unbalanced development stage, the coupling movement between various factors has a great destructive effect on the construction safety risk system of the subway shield tunnel. This model can not only identify the main risk factors affecting the safety risk system but also monitor the coupling status of the safety risk system in real time and master its development stage. By controlling the main risk factors affecting the safety risk system, the coupling degree of the safety risk system and the probability of the safety risk accident occurrence can be reduced.